Hotel 101 Yogyakarta Style Managemen Strategy in Increasing Room Occupancy Rate - Prasetyanto, Hermawan; Chandrawijaya, Robin (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
The research aims to analyze the promotional strategy at Hotel 101 Style Yogyakarta Malioboro in facing intense competition in the hospitality industry. The method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The data was analyzed using the SWOT method. The results showed that the hotel's main promotional strategies include the use of social media, cooperation with local agencies (Kemantren Pakualaman), and the use of an online reservation system from PHM. The system development methodology uses the System Development Life Cycle (SDLC) approach with a waterfall model. This research shows that the implementation of a web-based information system can improve the efficiency of recording transactions, speed up the process of making financial reports, and minimize human error. The test results show that the system is able to work according to user needs and can be a long-term solution in managing company financial data. The promotion strategy is considered effective in increasing consumer interest and hotel competitiveness.